Regulatory B cells in transplantation: roadmaps to clinic - Beckett, J; Hester, J; Issa, F; Shankar, S (Wiley, 2020)
Over the last two decades, an additional and important role for B cells has been established in immune regulation. Preclinical studies demonstrate that regulatory B cells (Breg) can prolong allograft survival in animal models and induce regulatory T cells. Operationally tolerant human kidney transplant recipients demonstrate B‐cell‐associated gene signatures of immune tolerance, and novel therapeutic agents can induce Bregs in phase I clinical trials in transplantation. Our rapidly expanding appreciation of this novel B‐cell subtype has made the road to clinical application a reality. Here, we outline several translational pathways by which Bregs could soon be introduced to the transplant clinic.